Investigation of shear‐flexural behavior of precast joints in prestressed reinforced concrete. (20th July 2020) - Zhi, Qing; Xiong, Xinfu; Kang, Liqun; Gong, Liangyong; Xiong, Jingang
Abstract: The behavior of precast concrete structures at the limit states of ultimate bearing capacity depends on the shear and shear‐flexural behavior of the joints between precast components, such as shear wall and beam–column joints, or between the precast component and footing. This study presented a series of tests on the shear‐flexural behavior of precast concrete joints applied in precast structures with high strength reinforcement. The tested parameters of the specimens included the joint type, shear‐span ratio, longitudinal reinforcement ratio, reinforcement type, and prestress. The tested results indicated that, for the precast joint specimens controlled by shear failure, the prestress by the high strength reinforcement can significantly improve the crack behavior, shear bearing capacity and stiffness of the precast structure. So it can emulate the monolithic cast‐in‐place specimen. For the precast joint specimens dominated by bending failure, the local deformation was mainly concentrated on the precast joint region, which affected the distribution of the plastic hinge region. To reduce the adverse effects by the precast joints, a grouting material with better performance should be used to improve the bond behavior of the reinforcement.